Spatiotemporal dynamics of water and sediment quality under multi-source pollution: A case study in the Jinjing Watershed, China - Lingling Tong; Feng Liu; Fatimah Md. Yusoff; Ahmad Zaharin Aris; Ahmad Fikri Abdullah; Yam Sim Khaw; Hui Teng Tan; Dejun Li; Murni Karim (PLoS ONE, 2025)
The dynamics of physicochemical properties within rivers are essential for understanding the health and functioning of aquatic ecosystems. This study investigated the spatial and seasonal variability of water quality in both water and sediment phases across rivers with different pollution sources in the Jinjing Basin: Tuojia River (TR), Tuojia River substream (TRS) (farmland), Guojia River (GR), Guojia River substream (GRS) (woodlands) and Jinjing River (JR) (residential). Samples were collected during wet and dry seasons and analyzed using multivariate statistical approaches. Farmland-dominated rivers (TR and TRS) exhibited the highest nutrient concentrations in both water and sediment phases, with elevated nutrients, soil organic matter (SOM), and dissolved organic carbon (DOC), driven by fertilizer runoff and organic inputs. In contrast, woodland rivers (GR and GRS) displayed the lowest nutrient levels, benefiting from dense vegetation and natural nutrient retention processes. Seasonal variability revealed higher nutrient concentrations in the water phase and increased levels of ammonium nitrogen (NH 4 + -N) and SOM in the sediment phase during the wet season. In the dry season, reduced flow enhanced photosynthesis, resulting in higher pH and dissolved oxygen levels in the water phase and elevated pH and DOC in sediment. Principal component analysis further confirmed that nutrient pollution is predominantly influenced by agricultural runoff during the wet season, while reduced runoff in the dry season allowed natural processes to dominate. The findings underscore the importance of managing nutrient loads in both water and sediment, especially in farmland areas to ensure the sustainability of water resource management in the Jinjing Basin.